2016
DOI: 10.1186/s12917-016-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of yeast Saccharomyces cerevisiae component binding to Mycobacterium avium subspecies paratuberculosis using bovine epithelial cells

Abstract: BackgroundSince yeast Saccharomyces cerevisiae and its components are being used for the prevention and treatment of enteric diseases in different species, they may also be useful for preventing Johne’s disease, a chronic inflammatory bowel disease of ruminants caused by Mycobacterium avium spp. paratuberculosis (MAP). This study aimed to identify potential yeast derivatives that may be used to help prevent MAP infection. The adherence of mCherry-labeled MAP to bovine mammary epithelial cell line (MAC-T cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…A potential concern about the preceding observations was that the reduction of E. coli internalization to epithelial cells was due to decreased cell viability. Li et al (2016) demonstrated that the yeast cell wall components reduced MAP binding to mammary epithelial cells, but this fact was partially attributed to decreased cell viability. Although some authors have worked with the MAP invasion process in MAC-T cells (Li et al 2016;Schwarz et al 2018), it is known that MAP is capable of inducing apoptosis in macrophages by a caspase-dependent or caspase-independent mechanism and mitochondrial damage (Periasamy et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A potential concern about the preceding observations was that the reduction of E. coli internalization to epithelial cells was due to decreased cell viability. Li et al (2016) demonstrated that the yeast cell wall components reduced MAP binding to mammary epithelial cells, but this fact was partially attributed to decreased cell viability. Although some authors have worked with the MAP invasion process in MAC-T cells (Li et al 2016;Schwarz et al 2018), it is known that MAP is capable of inducing apoptosis in macrophages by a caspase-dependent or caspase-independent mechanism and mitochondrial damage (Periasamy et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mammary epithelial cells (MAC-T) line have been widely used in adhesion/invasion assays (Li et al 2016) and thus was used in this experiment. MAC-T cells (kindly provided by Dr Yung-Fu Chang, Cornell University, Ithaca, USA) were cultured in T25 cell culture flasks (TPP Techno Plastic, St. Louis, MO, USA) at 37 C with 5% CO 2, containing Dulbecc os Modified Eagle Medium (DMEM; Gibco-BRL, Grand Island, NY, USA) supplemented with 10% heat inactivated fetal bovine serum (FBS; Sigma-Aldrich, St.…”
Section: Mammary Epithelial Cells and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, we have shown that CWC from specific S. cerevisiae strains can reduce attachment of Mycobacterium avium ssp. paratuberculosis (MAP) to different types of epithelial cells (Li et al, 2016). Mycobacterium avium ssp.…”
Section: Introductionmentioning
confidence: 99%